First clinical experiences with a direct acoustic cochlear stimulator in comparison to preoperative fitted conventional hearing aids - Busch, Susan; Kruck, Stefanie; Spickers, Dirk; Leuwer, Rudolf; Hoth, Sebastian; Praetorius, Mark; Plinkert, Peter K.; Mojallal, Hamidreza; Schwab, Burkard; Maier, Hannes; Lenarz, Thomas (Otology & neurotology, 2013)
Objective - Patients with moderate-to-severe mixed hearing losses (MHLs) are hard to provide sufficient benefit with currently available conventional hearing aids. Here, the long-term safety of a direct acoustic cochlear stimulator (DACS) and the effectiveness compared with conventional “high-performance” hearing aids were investigated. - Study Design - Prospective, within patient reference, nonrandomized, interventional multicenter clinical study performed at these 3 centers: Medical University Hannover, University of Heidelberg, and Helios Hospital Krefeld. - Patients and Intervention - Ten otosclerosis patients with severe-to-profound MHL were preoperatively fitted with state-of-the-art conventional hearing aids (HA). After 2 months of testing conventional HA, 9 of the patients decided to be implanted with a DACS. - Main Outcome Measures - Air conduction (AC) and bone conduction (BC) aided and unaided thresholds, speech discrimination before and after implantation and at 3, 6, and 12 months after activation. The subjective benefit was assessed by the Abbreviated Profile of Hearing Aid Benefit (APHAB). - Results - Preoperative hearing thresholds were preserved over the 12 month observation time after activation. Average functional gain (0.5-4 kHz) achieved with conventional HA was 47 dB compared with 56 dB with the DACS. Speech-in-noise tests revealed a lower SNR for DACS (3.1 dB) than for the HA (6.6 dB) and patients were more satisfied with the DACS. - Conclusion - The DACS significantly improved hearing, speech intelligibility, and satisfaction in patients with a severe-to-profound mixed hearing loss and can be considered a safe and useful alternative to conventional hearing aids.
Gesehen am 11.12.2020